PENERAPAN PEMBELAJARAN BERBASIS ETNOMATEMATIKA MOTIF BATIK SIDO MUKTI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 6 MATERI LUAS BELAH KETUPAT - Septya Rama Putri Kinaningtyas; Julianto; Dewi Anjarsari; Muhammad Juri; Fitria Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was (1) to determine the increase in student learning outcomes in ethnomathematics-based learning on the topic of rhombus area; 2) to determine student responses to ethnomathematics-based learning on the Sido Mukti batik motif. The study was conducted in class 6 of Petemon Elementary School, Surabaya with 26 students as research subjects. The type of research used Classroom Action Research (CAR). Data collection techniques were tests and response questionnaires. The research instruments were (1) tests aimed at measuring the increase in student learning outcomes in cycles I and II; (2) questionnaires intended to determine student responses to the ethnomathematics-based learning process on the Sido Mukti batik motif on the rhombus area material. Pre-cycle data obtained only 15% who completed the KKM. The results of the study after the implementation of ethnomathematics-based learning, learning outcomes from cycle I to cycle II increased. This is evidenced by the percentage of completion of learning outcomes in cycle I, which is 50% and cycle II 85%. The student response percentage was 90%, so overall they were happy and able to understand the extensive material on rhombuses. Thus, it is concluded that the application of ethnomathematics of Sido Mukti batik motifs on the material of the area of ​​a rhombus can improve students' learning outcomes.